Nutrition Status and Chronic Obstructive Pulmonary Disease: Can We Move Beyond the Body Mass Index?. (15th April 2019) - Raad, Samih; Smith, Cheryl; Allen, Karen
Abstract: Chronic obstructive pulmonary disease (COPD) represents an important global public health concern. Malnutrition is common in patients with COPD and often leads to worse outcomes for these patients. Recognition of overall nutrition status for patients with COPD is an important aspect of their care and treatment. Several methods have been studied that move beyond the standard/frequent use of body mass index alone. The purpose of this review is to summarize the current evidence for other tools to evaluate nutrition status in patients with COPD and highlight patients who may benefit from nutrition interventions.